A Mucinous Cystic Neoplasm of the Mesocolon Showing Features of Malignancy. (18th October 2012) - Mistry, Kiki; Penna, Marta; Dindyal, Shiva; Mukhtar, Hasan
Abstract : Mucinous cystic neoplasms are rare tumours of uncertain histogenesis. They arise from the ovaries, pancreas, and other intra-abdominal sites but more unusually from the mesocolon. They can present with abdominal pain, distension, or a palpable mass but are commonly an incidental finding. We describe the case of a 48-year-old woman who was found to have an incidental left pelvic cyst on computed tomography. Subsequent laparoscopic excision and histological analysis demonstrated the cyst to be a borderline malignant mucinous tumour arising from the mesocolon. Mucinous tumours should be considered in the differential diagnosis of all intra-abdominal cysts and treatment should be by surgical complete excision.